Teaching Reading Comprehension by Using Experience-Text-Relationship Method to Senior High School Students - Yuliana Mara Yuliantini; Aunurrahman Aunurrahman; Ageung Darajat (Edukasi: Jurnal Pendidikan, 2020)
AbstractThis research aimed to improve reading comprehension of public senior high school students by using Experience-Text-Relationship method. The research was done in two cycles and involved 31 eleventh-grade students of a public senior high school in SimpangDua, Ketapang in the Academic Year of 2018/2019. The researcher used observation field notes and reading tests to collect data of the study. A collaborator was involved during the observations and practices to build trustworthy of the study. The data from the observation field notes were analyzed qualitatively and the data from the reading test results were analyzed by using descriptive statistics. The analysis of the observation field notes shows that the students became active and polite, had high enthusiasm in the teaching and learning processes. The analysis of the reading test results also reveals that the students had improved their reading comprehension. In conclusion, Experience-Text-Relationship method can improve the students’ reading comprehension. AbstrakPenelitian bertujuan untuk meningkatkan pemahaman membaca siswa SMA negeri menggunakan metode Experience-Text-Relationship. Penelitian ini menggunakan dua siklus dan melibatkan 31 siswa kelas sebelas siswa di salah satu SMA negeri di SimpangDua, Kabupaten Ketapang pada Tahun Akademik 2018/2019. Peneliti menggunakan catatan lapangan observasi dan tes membaca untuk mengumpulkan data penelitian. Seorang kolaborator dilibatkan selama pengamatan dan praktik untuk membangun penelitian yang dapat dipercaya. Data dari catatan lapangan observasi dianalisis secara kualitatif dan data dari hasil tes membaca dianalisis dengan menggunakan statistik deskriptif. Analisis catatan observasi lapangan menunjukkan bahwa siswa menjadi aktif dan sopan, memiliki antusiasme yang tinggi dalam proses belajar-mengajar. Analisis hasil tes membaca juga mengungkapkan bahwa terjadi peningkatan pemahaman membaca siswa. Kesimpulannya, metode Experience-Text-Relationship dapat membantu meningkatkan pemahaman membaca siswa.